MO983EFFICACY AND SAFETY OF SWITCHING TO AZATHIOPRINE FOR MYCOPHENOLATE INDUCED DIARRHEA IN RENAL TRANSPLANT RECIPIENTS. (29th May 2021) - Sekmek, Serhat; Yildirim, Tolga; Koc, Neriman Sila; Onal, Ceren; Jabrayilov, Jabrayil; Yilmaz, Seref Rahmi; Arici, Mustafa; Altun, Bulent; Erdem, Yunus
Abstract: Background and Aims: Diarrhea is a common side effect of mycophenolate treatment in renal transplant recipients. In patients with mycophenolate induced diarrhea, one of the options is switching mycophenolate to azathioprine. In this study, we aimed to define the safety and efficacy of switching from mycophenolate to azathioprine for mycophenolate related diarrhea in renal transplant recipients. Method: A total of 177 patients, 59 of whom were switched to azathioprine due to diarrhea and 118 of which were matched control group without diarrhea that continued mycophenolate treatment, participated in this study. We analyzed the effect of switching to azathioprine from mycophenolate on amelioration of diarrhea and graft survival. Results: We observed that 89.8% of the patients who switched to azathioprine due to diarrhea had improved diarrhea complaints. Patients switched to azathioprine due do diarrhea had lower glomerular filtration rate (59 [15-125] vs. 74 [23-150] mL/min, p<0.001) and higher proteinuria (254 [49 – 15.500] mg/day vs. 184 [5 – 2329] mg/day, p<0.001) compared to control group before the switch. When patients switched to azathioprine were compared to a sub-group of 59 control patients who were matched to patients that switched to azathioprine in terms of baseline renal function and proteinuria in addition to demographic parameters, they had higher ten-years graft loss compared to patients that continued mycophenolate (p=0.03) (Figure 1 ). Particularly in patients with a glomerular filtration rate of less than 30 mL/min at the time of conversion, the risk of early graft loss was high. Conclusion: Although switching mycophenolate to azathioprine was an effective approach to improve diarrhea, this approach is associated with increased risk of graft loss.